Evaluation of different physical treatments in minimally processed green and red pepper (Capsicum annuum L.) - Rodoni, L M; Massolo, J F; Vicente, A R (Enfoque UTE, 2017)
This work evaluates three different conservation methods for red and green fresh-cut peppers. Red and green fruit were processed into sticks and treated as follows: A) water batch immersion (45 oC, 3 min) (TT), B) UV-C radiation (20 kJ m-2) or C) modified atmosphere storage (AM). Other group of pepper sticks were left untreated (control). The sticks were stored at 5 oC during 12 d. Fruit decay, soft-rot and respiratory rate were evaluated during storage. The three treatments were effective to reduce sticks deterioration and the treated fruit evidenced lower respiratory rate at 7 d of storage with respect to control. While the three methods were beneficial to maintain quality, in the red sticks the best results were found with TT and UV, mainly because the AM had less control of the soft-rot at the end of storage. In green sticks all the treatments were equally effective.